Pengembangan Media Pembelajaran Interaktif Berbasis Adobe Captivate Pada Mata Kuliah Dasar – Dasar Instalasi Listrik Di Prodi PTE Undiksha - I Putu Suka Arsa; Nyoman Santiyadnya; kefvi (Universitas Pendidikan Ganesha, 2023)
This reserch aims to develop an create a learning media tool in the form of Adobe Captivate based learning media for the subject Basic of Electrical Courses in the Electrical Engineering Education program at Undiksha University. The study addresses the issue of lack of knowledge in that can support learning the basics of Electrical Installation. It follows a Reserch and Development (R&D) approach.The reserch employs statistical analysis techniques, specifically percentage analysis, to process data from content experts, media experts, and student trials. Questionnaires are used as data collection instrumens for content eexperts, media experts, and students. The reserch findings indicate a validation test result of 96.87% from content experts, qualifying as highly suitable, a validation test result of 98.43% from media experts, qualifying as highly suitable, a small group trial with 5 respondents achieving a 100% result, qualifying as highly suitable, and a large group trial with 17 respondents achieving an 96.6% result, also qualifying as highly suitable. The developed learning tool, an Interactive Media Development based on Adobe Captivate for Basic Electrical Installation in the Electrical Engineering Education.